Pengaruh Review Produk, Influencer Marketing dan Persepsi Harga terhadap Keputusan Pembelian Moisturizer 5X Ceramide Skintific di Platform Tiktok Shop: Studi pada Gen Z di Kota Semarang - Aknes Astikasari; Mulyo Budi Setiawan (Wawasan : Jurnal Ilmu Manajemen, Ekonomi dan Kewirausahaan, 2026)
The skincare market is becoming more and more competitive, so it’s important for firms to know what makes people buy skincare products. This is especially true for Gen Z, who are big on social media and online shopping. One of the most popular places for members of Generation Z to get product details is TikTok Shop. The purpose of this research is to analyze how consumers in Semarang City made decisions to buy Skintific 5X Ceramide moisturizer based on their perceptions of its pricing, the effectiveness of product reviews, and influencer marketing. Using SPSS version 25, this quantitative study assessed data from 100 respondents chosen using a purposive sample method. According to the findings, influencer marketing does not impact purchase choices, but product evaluations and perceptions of prices do. When making skincare purchases on TikTok Shop, members of Generation Z are less likely to be swayed by influencer advertising and more likely to consider the experiences of other users and if the price is reasonable considering the product’s advantages.